Intrahippocampal transplantation of mesenchymal stromal cells promotes neuroplasticity - Coquery, Nicolas; Blesch, Armin (Cytotherapy, 2013)
Background aims: Multipotent mesenchymal stromal cells (MSC) secrete soluble factors that stimulate the surrounding microenvironment. Such paracrine effects might underlie the potential benefits of many stem cell therapies. We tested the hypothesis that MSC are able to enhance intrinsic cellular plasticity in the adult rat hippocampus. Methods: Rat bone marrow-derived MSC were labeled with very small superparamagnetic iron oxide particles (VSOP), which allowed for non-invasive graft localization by magnetic resonance imaging (MRI). Moreover, MSC were transduced with lentiviral vectors to express the green fluorescent protein (GFP). The effects of bilateral MSC transplantation on hippocampal cellular plasticity were assessed using the thymidine analogs 5-bromo-2′-deoxyuridine (BrdU) and 5-iodo-2'-deoxyuridine (IdU). Behavioral testing was performed to examine the consequences of intrahippocampal MSC transplantation on locomotion, learning and memory, and anxiety-like and depression-like behavior. Results: We found that intrahippocampal transplantation of MSC resulted in enhanced neurogenesis despite short-term graft survival. In contrast, systemic administration of the selective serotonin re-uptake inhibitor citalopram increased cell survival but did not affect cell proliferation. Intrahippocampal transplantation of MSC did not impair behavioral functions in rats, but only citalopram exerted anti-depressant effects. Conclusions: This is the first study to examine the effects of intrahippocampal transplantation of allogeneic MSC on hippocampal structural plasticity and behavioral functions in rats combined with non-invasive cell tracking by MRI. We found that iron oxide nanoparticles can be used to detect transplanted MSC in the brain. Although graft survival was short, intrahippocampal transplantation of MSC resulted in long-term changes in hippocampal plasticity. Our results suggest that MSC can be used to stimulate adult neurogenesis.
Gesehen am 08.10.2018
Available online 8 January 2013